Residencias universitarias de Medellin ciudad para estudiantes (2015)
Medellin is a city of transformations, one of them is what has been submitted to become a city that offers services. One of those services is education. As the years go by, there are more students coming from other regions, both in the department of Antioquia, as other Colombian departments, and elsewhere in Colombia, Located those students, in areas surrounding major universities and brokers in order to ensure economy and time saving when they´re traveling The project aims to generate a collective housing development, where they can show the dynamics of the city, including internal growth and a direct connection to a system of cheap transport, like the use of bikes, systems like this produce suffi ciently access at different universities in the city.